Decidualization Process Induces Maternal Monocytes to Tolerogenic IL-10-Producing Dendritic Cells (DC-10) - Gori, Soledad; Soczewski, Elizabeth; Fernández, Laura; Grasso, Esteban; Gallino, Lucila; Merech, Fatima; Colado, Ana; Borge, Mercedes; Pérez Leirós, Claudia; Salamone, Gabriela; Ramhorst, Rosanna (Frontiers in Immunology, 2020)
The decidualization process involves phenotypic and functional changes of endometrial stromal cells to sustain endometrial receptivity and the participation of immunoregulatory factors to maintain immune homeostasis. In this context, tolerogenic denditric cells (DC) can induce regulatory T cells, which are essential to manage the pro- to anti-inflammatory transition during embryo implantation. Recently, Myeloid Regulatory Cells (MRCs) were proposed as immunosuppressant and tolerance inducer cells, including the DC-10 subset. This novel and distinctive subset has the ability to produce IL-10 and to induce type 1 Tregs (Tr1) through an HLA-G pathway. Here we focus on the impact of the decidualization process in conditioning peripheral monocytes to MRCs and DC-10 subset, and their ability to induce regulatory T cells. An in vitro model of decidualization with the human endometrial stromal cell line (HESC) decidualized by medroxyprogesterone and dibutyryl-cAMP was used. Monocytes isolated from peripheral blood mononuclear cells from healthy women were cultured with rhGM-CSF + rhIL-4 and then, the effect of conditioned media from decidualized (Dec-CM) and non-decidualized cells (Non-dec-CM) was tested on monocyte cultures. We found that Dec-CM inhibited the differentiation to CD1a+CD14- immature DC profile in a concentration-dependent manner. Also, Dec-CM significantly increased the frequency of CD83+CD86low and HLA-DR+ cells in the monocyte-derived culture. These markers, associated with the increased production of IL-10, are consistent with a MRCs tolerogenic profile. Interestingly, Dec-CM treatment displayed a higher expression of the characteristic markers of the tolerogenic DC-10 subset, HLA-G and ILT2/CD85j; while this modulation was not observed in cultures treated with Non-dec-CM. Moreover, when monocyte cultures with Dec-CM were challenged with LPS, they sustained a higher IL-10 production and prevented the increase of CD83, CD86, IL-12p70 and TNF-α expression. Finally, the DC-10 subset was able to induce CD4+HLA-G+ regulatory T cells subset. These results suggest that the decidualization process might induce different subsets of MRCs, like DC-10, able to induce regulatory T cells as a novel CD4+HLA-G+ subset that might play an immunoregulatory role in embryo implantation.